Peripheral Nerve Conduction And Sympathetic Skin Response Are Reliable Methods to Detect Diabetic Cardiac Autonomic Neuropathy - Lin, Xiaopu; Chen, Chuna; Liu, Yingshan; Peng, Yu; Chen, Zhenguo; Huang, Haishan; Xu, Lingling (Frontiers in Endocrinology, 2021)
Aim: This study aimed to investigate the role of nerve conduction studies (NCS) and sympathetic skin response (SSR) in evaluating diabetic cardiac autonomic neuropathy (DCAN). Methods: DCAN was diagnosed using the Ewing test combined with heart rate variability analysis. NCS and SSR were assessed by electrophysiological methods. The association between NCS/SSR and DCAN was assessed via multivariate regression and receiver-operating characteristic analyses. Results: The amplitude and conduction velocity of the motor/sensory nerve were found to be significantly lower in the DCAN+ group (all P < 0.05). A lower amplitude of peroneal nerve motor fiber was found to be associated with increased odds for DCAN (OR 2.77, P < 0.05). The SSR amplitude was lower while the SSR latency was longer in the DCAN+ group than in the DCAN– group. The receiver-operating characteristic analysis revealed that the optimal cutoff points of upper/lower limb amplitude of SSR to indicate DCAN were 1.40 mV (sensitivity, 61.9%; specificity, 66.3%, P < 0.001) and 0.85 mV (sensitivity, 66.7%; specificity, 68.5%, P < 0.001), respectively. The optimal cutoff points of upper/lower limb latency to indicate DCAN were 1.40 s (sensitivity, 61.9%; specificity, 62%, P < 0.05) and 1.81 s (sensitivity, 69.0%; specificity, 52.2%, P < 0.05), respectively. Conclusions: NCS and SSR are reliable methods to detect DCAN. Abnormality in the peroneal nerve (motor nerve) is crucial in predicting DCAN. SSR may help predict DCAN. Keywords: Diabetic cardiac autonomic neuropathy, Ewing test, heart rate variability, nerve conduction, sympathetic skin response, T2DM